Study on Influence of Asymmetric Air Gap on Damping Performanceof Eddy Current Retarder - WU Hongyu;YAN He;DONG Yujie;DIAO Xingzhong (Yuanzineng kexue jishu, 2023)
The double-sided permanent magnet eddy current retarder, equipped with a set of magnets at a certain air gap on both sides of the conductor disk to make it rotate in the alternating magnetic field to generate the damping torque, has important applications in the field of high temperature gas cooled reactor control rod drop speed limit. The double-sided magnet structure can achieve greater magnetic flux, make the structure more compact, and balance the axial forces on both sides of the conductor disk. However, due to the influence of part machining accuracy and assembly deviation, it is difficult to accurately control the air gap width on both sides of the conductor disk to be equal. And for convenience, only one side of the air gap is usually adjusted when adjusting damping in engineering applications, which increases the asymmetry of the air gap width. For different requirements such as optimal torque or maximum critical speed, the conductor disk generally selects nonmagnetic materials with high conductivity or ferromagnetic materials with high permeability. In this paper, the influence of asymmetric air gap on the damping torque was studied. First, the main magnetic path of the eddy current retarder was analyzed, the two-dimensional magnetic equivalent circuit was established, and the influence of the asymmetry degree δ of the air gap on the main magnetic flux was qualitatively analyzed. Second, based on the three-dimensional finite element simulation, the magnetic field distribution, air gap magnetic induction intensity, damping torque, and axial force in the case of ferromagnetic and nonmagnetic conductor disks were compared. Finally, the experimental verification was carried out. The results show that, for the double-sided permanent magnet eddy current device, there are two main magnetic circuits, one is very sensitive to δ, while the other is almost insensitive to it. The sensitivity of the damping torque to δ can be reduced by adjusting the magnetic resistance of the magnetic circuit to increase the proportion of the insensitive main magnetic circuit flux in the total main magnetic flux. In the running state, the main magnetic circuit transfers when ferromagnetic and nonmagnetic conductor disks are used respectively. With the constant total air gap width, the damping torque and axial force are not sensitive to δ when the nonmagnetic conductor disk is used, but they show a significant sensitivity when the ferromagnetic conductor disk is used. For the permanent magnet eddy current device with a double-sided magnet structure, the nonmagnetic material conductor can reduce the sensitivity to the air gap deviation on both sides.